Footwear Industry Investigation: The Impact of Attitude and Habits on Use Intention in Generation Z Based on Theory of Planned Behavior - Pradana, Ferdika Adhi; Marsasi, Endy Gunanto (Universitas Brawijaya, Indonesia, 2024)
The increasingly tight competition in the sneaker footwear industry encourages companies to formulate targeted marketing strategies, focusing on creating relevant added value for consumers and building loyalty and strong long-term relationships with consumers. Although the sneaker footwear industry is growing rapidly, in-depth research linking economic benefits, trust, hedonic benefits, attitudes, and habits to the intention to use sneaker products still needs to be completed. This study aims to identify and analyze the influence of attitudes and habits on the use intention of sneaker users in several major cities in Indonesia. The theory of planned behavior is used to understand human behavior. It highlights a person's attitudes, subjective norms, beliefs, and behavior. This study uses a quantitative approach. Primary data was collected by distributing questionnaires to 185 respondents and analyzed using Structural Equation Modeling (SEM). Data analysis uses SPSS 29 and Amos Graphic 26 software. The results of this study indicate that economic benefits and hedonic benefits have a significant effect on attitude, while trust does not have a significant effect on attitude. This study reveals that economic benefits, hedonic benefits, and habits have a significant effect on use intention, and attitude has a significant positive effect on habits. The novelty of this study's research is the addition of habits variables, which are expected to provide a deeper view of the influence of consistency and repetition of consumer behavior on use intention toward sneakers. The findings of this study provide important insights for companies to develop effective marketing strategies that utilize economic benefits, trust, hedonic benefits, attitudes, and habits to increase product use intention.